2023
DOI: 10.2147/jir.s429892
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Coagulation are Two Interconnected Pathophysiological Pathways in Atrial Fibrillation Pathogenesis

Lusine Hazarapetyan,
Parounak Zelveian,
Svetlana Grigoryan

Abstract: Atrial fibrillation (AF) is associated with elevated levels of clotting factors such as tissue factor (TF) and factor XII (FXII). Various inflammation markers, such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and high-sensitive C-reactive protein (hs-CRP), have also been associated with AF. This study explores the relationship between inflammation markers and coagulation activity, including their impact on heart structural changes in these patients. Methods: We observed 283 patients with nonvalvu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Inflammation is another important link between AF and depression or anxiety. Studies have shown that patients with AF have significantly higher serum levels of ultrasensitive C-reactive protein and interleukin 6, and anxiety and depression are strongly associated with these two inflammatory mediators[ 46 , 47 ]. The renin-angiotensin-aldosterone system (RAAS) is also implicated in AF and mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is another important link between AF and depression or anxiety. Studies have shown that patients with AF have significantly higher serum levels of ultrasensitive C-reactive protein and interleukin 6, and anxiety and depression are strongly associated with these two inflammatory mediators[ 46 , 47 ]. The renin-angiotensin-aldosterone system (RAAS) is also implicated in AF and mental disorders.…”
Section: Discussionmentioning
confidence: 99%